Venous diameter changes in chronic active multiple sclerosis lesions - Weber, Claudia Ellen; Kraemer, Matthias; Dabringhaus, Andreas; Ebert, Anne; Platten, Michael; Gass, Achim; Eisele, Philipp (Journal of neuroimaging, 2021)
BACKGROUND AND PURPOSE To investigate the temporal evolution of venous diameter in chronic active and nonenhancing shrinking multiple sclerosis (MS) lesions in a longitudinal magnetic resonance imaging (MRI) study including susceptibility-weighted images (SWI). METHODS We compared the venous diameter in chronic active and nonenhancing shrinking lesions to the venous diameter in nonenhancing stable lesions on two 3 T MRI data sets obtained 12 months apart. Chronic active and nonenhancing shrinking lesions were identified by Voxel-Guided Morphometry. Coregistered, overlaid fluid-attenuated inversion recovery/SWI were analyzed for the presence of a central vein. Quantitative calculation of the venous diameter for each time point was performed on the reconstructed veins. RESULTS Sixty-two relapsing-remitting MS patients (50 women; mean age: 36 ± 11 years; mean disease duration: 4 ± 7 years) were included in the study. Overall, we identified 222 chronic MS lesions (48 chronic active, 48 shrinking, 126 stable) with a corresponding intralesional central vein. On baseline MRI, the mean venous diameter did not statistically differ between all subgroups, whereas on follow-up MRI, the mean intralesional venous diameter was smaller in chronic active (0.92 ± 0.15 mm) and shrinking lesions (0.90 ± 0.19 mm) compared to stable lesions (1.10 ± 0.18 mm; P < .001). CONCLUSION Our findings demonstrate venous narrowing in chronic active and nonenhancing shrinking MS lesions. The smaller diameter of intralesional veins during follow up in these lesions may reflect structural, degenerative, and metabolic changes due to chronic inflammation, (perivascular) fibrosis, collagenous thickening, and increased levels of oxygenated hemoglobin.
First published: 03 December 2020
Gesehen am 20.08.2021